A Study on the Scheduled Castes and Scheduled Tribes in Haryana: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India is the home to over 2,000,000 people, who now prefer to be called Dalits (oppressed), but are officially known as scheduled castes. In 2011, its 201.4 million population was larger than the total population of Brazil, the fifth most populous country in the world (199 million in 2012). This or that sub-caste of the programmed castes belongs to somewhere any sixth individual in India. They not only have a rather big population but still are increasing increasingly. 51.3 million Specified caste population rose to 201.4 million in 2011 and the average compound growth trend for India over the same era was 2.3 percent against 2.0 percent.